Study on Effect of Producing Region on the Metabolome Composition of Rice - LIU Fu-ying; CHEN Xue-feng; WANG Xin; CHEN Guo-yan; GUO Ying; SUN Jing-han; YANG Shui-yan; NIE Xu-heng (Liang you shipin ke-ji)
Yunhui 290 is one of the characteristic indica rice varieties in Yunnan Plateau. Due to its unique flavor, Yunhui 290 is widely loved by consumers. In this study, the Yunhui 290 rice metabolome from 3 different producing areas was andyzed using a widely targeted metabolomics approach, and 1003 metabolites were identified. By principal component analysis (PCA) and partial least square discriminant analysis (OPLS-DA), the results showed that the numbers of differential metabolites between the comparison groups (GJYH290 vs MLYH290, MZYH290 vs GJYH290, MZYH290 vs MLYH290) were 130, 180, and 192, respectively, only 6 different metabolites were common to all three comparison groups, with the main metabolic pathways involving amino acid metabolism and flavonoid metabolism. The top 10 most significantly upregulated and downregulated metabolites with the largest fold changes in the 3 comparison groups were mainly flavonoids, phenolic acids, nucleotides and their derivatives. This study provides valuable insights into the metabolic composition and differences of rice from different producing regions.